Fatty acids from multiple species of invertebrates, teleosts, elasmobranchs, and marine mammals sampled in Cumberland Sound, 2007-2009 - Fisk, Aaron; McMeans, Bailey; Arts, Michael (Canadian Cryospheric Information Network, 2012)
Samples of macroaglae (Fucus distichus), several zooplankton species (e.g. Calanus hyperboreus, Sagitta spp.), benthic invertebrates (e.g. scallop Chlamys islandica, snail Buccinum cyaneum, clam Hiatella arctica), teleosts (herring Clupea harengus, capelin Mallotus villosus, char Salvelinus alpines, sculpin Myoxocephalus scorpioides (adults and larvae), turbot Reinhardtius hippoglossoides), two elasmobranchs (arctic skate Amblyraja hyperborea, Greenland shark Somniosus microcephalus), two pinnipeds (harp seal Pagophilus groenlandicus, ringed seal Pusa hispida) and two cetacean (beluga whale Delphinapterus leucas , narwhal Monodon monoceros) species were collected from Cumberland Sound (Nunavut). Zooplankton were sampled by surface horizontal tows and vertical hauls using a plankton net. Benthic invertebrates were sampled by ponar or dip net, herring, char and sculpin by gillnet, capelin by dip net and turbot, arctic skate and Greenland sharks by bottom long line. Marine mammals were sampled during Inuit subsistence hunts. Fatty acids were extracted from the total lipid fraction of whole zooplankton, soft tissues of benthic molluscs, muscle tissues of fish and elasmobranchs and blubber tissue of marine mammals. One exception is the Greenland shark whose liver, muscle and blood plasma were analyzed for fatty acids. Tissue samples were first freeze dried and homogenized and lipids were extracted using 2:1 chloroform:methanol. Percent total lipid (on a dry weight tissue basis) was determined gravimetrically. Fatty acid methyl esters were generated via sulfuric acid in methanol (1:100 mixture) and analyzed via gas chromatograph coupled with a flame ionization detector. Fatty acids were identified using known fatty acid standards. Samples were collected during both summer/open water (early August) and late winter/ice cover (early April) to explore seasonal changes in species' diets. : Purpose: As the largest fish and most prolific eater in the Arctic seas, the Greenland shark is a very unique vertebrate in the Arctic ecosystem. Given their diet, Greenland sharks hold a position in the food web similar to that of polar bears. Little is known about how these sharks behave or how their behaviour might shift in response to changes in climate. Given their importance in the Arctic food web, this project is assessing the feeding ecology and behaviour of the Greenland shark under different ice conditions to determine how different environments affect this fish. This assessment involves the analysis of fatty acids from multiple species of invertebrates, teleosts, elasmobranchs, and marine mammals sampled in Cumberland Sound in 2007, 2008 and 2009. : Summary: Not Applicable